The Use of The Canva Application in The Learning of Maharah Kitabah at The Islamic Boarding School Prof. Hamka Maninjau Class VII - Azizah, Wardah; Oktavia, Nur Afni; Mudinillah, Adam (Scientechno: Journal of Science and Technology, 2022)
Quality of education is the ability of a school to organize efficiently and operationally on elements related to schools so as to produce added value to these components according to applicable norms/standards. Management of improving the quality of education in schools is a quality improvement method that relies on the school's education itself, implementing several techniques, based on the availability of qualitative data and empowering all school components to continuously advance the capacity and ability of school organizations to meet the needs of students and others. . What is meant by integrated quality management is freedom of opinion. Freedom of expression will create a dialogical climate between students and educators, as well as between students and the madrasa head, the conclusion is freedom of opinion and openness between all madrasah citizens.